Carlos Drummond de Andrade: o poeta na condição de leitor - Silva, Luciana Bessa (2021)
The greatest mission of the writer Carlos Drummond de Andrade (1902-1987) was to be an “action poet” and the only weapon he had was the word, his accomplice and inseparable companion. His work is long and multiple: between Alguma poesia (1930), initial work, and Farewell (1996), posthumous work in which he recorded from loves to pains, skepticism, life and death drives, childhood and homeland. This “public poet”, besides being an observer, was a photographer and an everyday reader. He first read the world, then the words. He collected some and appropriated others for the construction of his Poetics, becoming a fighter, or better, a writer. He refused to rhyme words, to write lines about birthdays and personal incidents. He found some “stones in the way”, but he created his own method: the lost and released words at the mercy of the writers. In this constant and inglorious struggle, he deciphered enigmas, constructed new words and made others more beautiful, joined the cause of men who suffer amid the uncertainties brought by the capitalist machine, came to think that poetry was incommunicable, but aware that the present time it was his subject, he urged everyone to stay with “Hand in Hand”, because he understood poetry as resistance. As a writer, he was first and foremost a reader. In “Childhood” he read the magazines Tico-Tico (1905) and Fon-Fon (1907). As a teenager, together with the “boys from Belo Horizonte” he founded Revista (1925), the largest disseminator of modernist ideas in Minas Gerais and participated in several others: Revista Verde (1927) and Leite Criolo (1929) also in Minas Gerais. Therefore, the object of this research is the analysis of the readings that influenced the writer Carlos Drummond de Andrade through the dialogue that his poetry establishes with other writers, painters, photographers, characters, literary critics of Brazilian Literature and Foreign Literature. Therefore, we reflect on the categories: Drummond, influence, intertextuality, reader and writer. The research is divided into four phases: in the first, we present an overview of the 20th century, since Drummond is a writer of that period and we share the idea that is through the historical context that we best understand a writer. In the second phase, we revisit the concept of influence and intertextuality and experience it within the poet's own work, since dialogicity is the condition of language's existence. Although our focus was on his poetics, we went through the books more closely: Alguma poesia (1930), A rosa do povo (1945), Viola de bolso and Viola de bolso entrecortada (1952-1955), Discurso de primavera e algumas sombras (1977) and Amar se aprende amando (1985). In the third, after the discussion about the reading process and its importance, we witness the loving encounter between the reader Carlito and the books that marked his childhood and adolescence, to understand his interpretation of the world in maturity. To understand the formation of this critical reader, we went to the work: Boitempo I – Memória, Boitempo II – Menino antigo and Boitempo III – Esquecer para lembrar. In the last phase, the boy reader becomes a writer, so we reflect on the process of Drummondian reading and writing between the universe of poetry and the universe of prose. We use the hermeneutic method, based on the conceptions of Eduardo Portella, as the work’s methodologically bases. At certain moments, it was necessary to highlight the biographical (José Maria Cançado), historical (Gilberto de Melo Kujawski, Eric Hobsbawn), critical (Afonso Romano de Sant’ Anna, Antonio Cândido, John Gledson, Otto Maria Carpeaux etc) and stylistic aspects (Hélcio Martins, Emanoel de Moraes etc). Carlito first read the world, then the words. His first reading experiences were through magazines. He was taken to the “country of literature” by his family, friends and teachers. The experience at the Grêmio Dramático e Literario Arthur de Azevedo, the literary and non-literary conversations at Café Estrela the trips to Alves Bookstore and the non-traditional work with translation contributed to Carlos Drummond de Andrade, from an early age, became an astute, sensitive and critical reader of himself and the reality around him.